Balibar, citizenship, and the return of right populism. (March 2020) - Pfeifer, Geoff
Arendt famously pointed out that only citizenship actually confers rights in the modern world. To be a citizen is to be one who has the 'right to have rights'. Arendt's analysis emerges out of her recognition that there is a contradiction between this way of conferring rights as tied to the nation-state system and the more philosophical and ethical conceptions of the 'rights of man' and notions of 'human rights' like those championed by thinkers such as Immanuel Kant who understands rights belonging universally to all humans as a result of facts having to do with what it means to be human. Étienne Balibar, in his recent work, adds to this by pointing out that there is a contradictory movement between this universalizing tendency in philosophical thought and the production of the citizen-subject out of the exclusionary acts of law and force. In this article, I put Balibar's work in dialogue with the contemporary moment where we are witnessing the re-emergence of a nativist right populism. I use Balibar to help distinguish between three modes of political existence that we find today. Two of these three are more or less well understood. They are the non-citizen, who has no – or almost no – rights in a given nation-state and the citizen who enjoys the full benefit of the rights a given nation-state has to give. The third category is what I term the 'nominal citizen'. This last category is somewhere in between full citizenship and non-citizenship. Individuals in this last category have rights in name but are largely unable to exercise them. Understanding this last category can, among other things, help us at least partially make sense of the return of right populism and also help us see the ways in which the modern category of citizenship, with its contradictions as elaborated by Balibar, can provide a means for resistance.